2016
DOI: 10.1590/0102-6720201600010007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Preoperative Ultrasonography Reports With Intraoperative Surgical Findings in Cholelithiasis

Abstract: Background: Laparoscopic cholecystectomy is widely used for cholelithiasis. Abdominal ultrasonography often precedes this operation and can prove diagnosis, as well as helps in showing possible complications during the perioperative period. Aim: Evaluate the description of variables of gallbladder and bile ducts present in reports of preoperative abdominal ultrasonography in cholelithiasis comparing with surgical findings. Methods: Were studied 91 patients who underwent elective laparoscopic cholecystectomy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…The main risk associated with the LC appears to be a higher incidence of bile duct injury than open cholecystectomy, 0.3-0.8% 9 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The main risk associated with the LC appears to be a higher incidence of bile duct injury than open cholecystectomy, 0.3-0.8% 9 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated, nowadays, that 85% of the patients with cholecystolithiasis keep asymptomatic for at least 10 years. In the last two decades, the knowledge and management evolved in a meaningful way, and a lot of clinical and microbiological parameters have been studied, just like the way how antibiotics and defense systems of biliary tract interfere with the evolution of the infections in bile duct 1 , 4 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The level of sensitivity obtained in the study is quite comparable to that reported in some previous studies for CT, MRCP, PTC, and ERCP ( 3 , 15 , 26 , 27 ) . We believe that the meticulous, protocol-driven ( 11 , 12 ) use of ultrasound for the diagnosis of obstructive jaundice would further help to improve surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…In resource-poor settings, ultrasound is often the only readily available method, with many of the other modalities being too expensive or unavailable to many patients. Furthermore, abdominal ultrasound is considered to be the first initial imaging procedure in obstructive jaundice ( 1 , 5 , 11 , 12 ) . Ultrasonography could also be used for some imaging-guided hepatobiliary interventions.…”
Section: Introductionmentioning
confidence: 99%